2020
DOI: 10.1177/2167702620916454
|View full text |Cite
|
Sign up to set email alerts
|

Contact With an Ex-Partner Is Associated With Psychological Distress After Marital Separation

Abstract: In this study, we examined the association between naturalistically observed in-person contact with an ex-partner and separation-related psychological distress (SRPD). One hundred twenty-two recently separated adults were assessed using the Electronically Activated Recorder on three occasions across 5 months. The association between in-person contact with an ex-partner, as a between-person variable, and concurrent SRPD was not reliably different from zero, nor was the time-varying effect of in-person contact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…three weekends, each separated by 2 months) with a recording rate of 30 seconds every 12 minutes. For more details on this sample, see Hasselmo et al (2018), Bourassa, Tackman, Mehl, and Sbarra (2019), and O'Hara, Grinberg, Tackman, Mehl, and Sbarra (2020).…”
Section: Methodsmentioning
confidence: 99%
“…three weekends, each separated by 2 months) with a recording rate of 30 seconds every 12 minutes. For more details on this sample, see Hasselmo et al (2018), Bourassa, Tackman, Mehl, and Sbarra (2019), and O'Hara, Grinberg, Tackman, Mehl, and Sbarra (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, our results suggest that just analysing the average amount of time a person spends talking can miss important relationships between personality and style of socializing. Our work adds to the growing literature on personality dynamics (Hopwood, Zimmermann, Pincus, & Krueger, 2015; Robinson & Gordon, 2011; Read et al, 2010; Sosnowska, Kuppens, De Fruyt, & Hofmans, 2019; Wright, Hopwood, & Simms, 2015) and the dynamics of socializing (Dishion & Snyder, 2004; Hollenstein, 2007; Lavictoire, Snyder, Stoolmiller, & Hollenstein, 2012; Schelling, 1998). We present the first instance (to the best of our knowledge) of relating non–linear socializing dynamics assessed through ambulatory assessment to personality traits (but see Gundogdu et al, 2017 and Wang et al, 2018, for related analysis strategies, and Stachl et al, 2020, for some linear dynamic measures).…”
Section: Discussionmentioning
confidence: 72%
“…Person and situation are in continual interaction, forming a feedback loop. These dynamics allow for self–regulation and the pursuit of key goals (Read, Smith, Droutman, & Miller, 2017). For example, recent research has found that personality states ‘enacted’ at a given moment were related to the goals individuals were pursuing at that moment (McCabe & Fleeson, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations